Morphological and molecular analysis of rose cultivars from the Grandiflora and Kordesii garden groups - S. S. Yudanova; O. V. Dorogina; O. Yu. Vasilyeva (Вавиловский журнал генетики и селекции, 2024)
The breeding of remontant rose cultivars that are resistant to diseases and adverse conditions, with high decorative value and continuous flowering is the most important task during work with the gene pool of garden roses. Currently, intercultivar hybridization within a single garden group has largely outlived its usefulness. It is necessary to breed for highly decorative forms or cultivars that have outstanding resistance, morphological characters and patterns of seasonal rhythms, and use these plants as parental forms in further breeding. This study represents a comparative analysis of rose cultivars from two garden groups, Grandiflora (Gurzuf, Lezginka, Korallovy Syurpriz, Queen Elizabeth, Komsomolsky Ogonyok, Love) and Rosa Kordesii (Letniye Zvyozdy, Dortmund, Gutsulochka). These cultivars proved themselves during many years of testing in harsh climatic conditions. The objectives of the study were to determine the genetic relationship within the groups and to assign phenotypically different cultivars to one or another garden group. The analysis was carried out by morphological, phenological and ISSR markers. According to the phenological observations on the Grandiflora cultivars, Komsomolsky Ogonyok had later budding and flowering stages. Polymorphic data generated from the ISSR markers showed that this cultivar was the most distant from the others and formed a separate cluster on the dendrogram. A comparison of the morphological characters (flower diameter, number of petals, peduncle length, bush height) showed a significant difference (p < 0.05) between Komsomolsky Ogonyok and the other Grandiflora cultivars. A dendrogram based on a molecular analysis showed a lack of close relationships between Komsomolsky Ogonyok and the Kordesii group, which formed a separate cluster. A pairwise comparison of the morphological characters in Komsomolsky Ogonyok with the Kordesii group revealed a significant (p < 0.05) difference in three of the four characters studied. The exceptions were flower diameter when comparing with Dortmund and Letniye Zvyozdy and peduncle length when comparing with Gutsulochka. Although Komsomolsky Ogonyok has a pattern of seasonal development similar to Dortmund in the Kordesii group, the molecular analysis did not assign the former to this group of roses. The cultivars that have valuable characters that no average rose does and that are phenotypically different from such roses represent the most valuable breeding material.